Adherence to combination antiretroviral therapy among orphaned children in Dar es Salaam, Tanzania - Sabina F. Mugusi; Nassoro Mopei; Omary Minzi (AOSIS, 2019)
Background: Adherence to combination antiretroviral therapy (cART) among HIV-infected children is often complicated by various factors including medication formulation, dosing frequency, drug toxicities, age and developmental stage, psychosocial and behavioural characteristics of both children and caregivers and can additionally be complicated by being an orphan. Objectives: This study was aimed at determining the factors and the extent of their influence on cART adherence among HIV-infected orphaned children attending Care and Treatment Centres (CTCs) in Dar es Salaam, Tanzania. Methods: A cross-sectional study was performed, which assessed adherence in HIV-positive orphaned children aged 2-14 years receiving nevirapine (NVP) based cART for at least 6 months. Data was collected using questionnaires administered to primary caregivers of HIV-infected orphaned children, the review of medical files, and the laboratory measurement of NVP plasma concentrations and CD4 counts. Adherence to cART was determined based on caregivers' self-report, consistency of clinic attendance and NVP plasma concentrations. Results: Among the 216 enrolled orphaned children, adherence to cART was found to be 79.6%, 82.9% and 72.2% respectively based on caregivers' self-report, clinic attendance and NVP plasma levels. Significant reductions in NVP concentrations ( 3 µg/mL) were seen among children with poor immunological outcomes, poor clinic attendance (p  0.05) and were suggested by caregivers' self-reported adherence (p = 0.06). Adherence challenges identified by caregivers included financial constraints (87.5%), lengthy waiting times at clinics (75.5% spent 2 h at the clinic) and low HIV knowledge among caregivers. Conclusion: Significant numbers of HIV-infected orphans have poor adherence to cART ranging between 17% and 28% based on different assessment methods. Inadequate caregiver knowledge of HIV/AIDS, long clinic waiting times and forgetfulness were identified as barriers to cART adherence in these orphans.